1913. (21st April 2016) - Unknown
Abstract : Lovely day. In the afternoon Reynolds, Atkinson and I walk over to Lelant where most of the big St. Ives boats lie up between seasons. Many of them, I fear, will never leave their moorings again. A mournful spectacle – 80 sail or so of the once brilliant fleet of St. Ives. Can motor-power avail to save them?